Assessing brand personality associations of top of mind wine brands - Brochado, A.; Vinhas da Silva, R.; LaPlaca, P. (International Journal of Wine Business Research, 2015)
Purpose – The purpose of this paper is to examine brand knowledge of wines produced in a selected Portuguese viticulture area. More specifically, we intend to understand how consumers organise brands that have the highest awareness in their memory in terms of perceived personality traits. Design/methodology/approach – A survey was developed to assess brand awareness of Portuguese green wine brands and brand personality using Aaker’s brand personality framework. Multiple correspondence analysis was used in this study to present the relative positioning of the top-of-mind green wine brands. Findings – Despite the large number of green wine brands available on the market, six brands dominate in terms of brand awareness. Top-of-mind green wine brands are marked with clear and distinctive brand personality, and a small subset of brand personality attributes serve as significant criteria for brand positioning. Practical implications – The results of the present study could be beneficial for academics and practitioners, as it reveals that the top-of-mind brands within a specific viticulture area could exhibit a clear positioning based on personality traits. Therefore, brand personality traits might provide a mechanism for wine managers to distinguish or differentiate their wines. Originality/value – This work contributes to the findings of previous studies held to study brand personality perceptions. From a theoretical point of view, this paper reflects the usage of one the most popular instruments for brand personality measurement in a wine market context.